Impact of irradiation conditions on therapy of Lewis lung carcinoma in mice using glucose-ethylenediamine carbon dots - Pavlo Lishchuk; Halyna Kuznietsova; Taisa Dovbynchuk; Nataliia Dziubenko; Liudmyla Garmanchuk; Sergei Alekseev; Mykola Isaiev; Nataliya Pozdnyakova; Artem Pastukhov; Nataliya Krisanova; Tatiana Borisova; Vladimir Lysenko; et al. (BMC Cancer)
Abstract Background nowadays, the photoacoustic imaging is in the mainstream of cancer theranostics. In this study the nanoparticles with previously proven photoacoustic imaging properties, i.e. glucose-ethylenediamine carbon dots (GE-NPs), were tested for photoacoustic cancer therapy. Methods nanoparticle biocompatibility was analyzed in cell toxicity and neurotoxicity experiments ex vivo. Biochemical parameters were analyzed in animal experiments in vivo after intramuscular implantation of Lewis Lung carcinoma cells into the C57/Black mouse line. Results GE-NPs at concentrations of 0.1–1.0 mg/ml did not change the extracellular level, exocytotic and transporter-mediated release, as well as the initial rate of uptake and accumulation of L-[14C]glutamate in isolated rat brain nerve terminals. GE-NP-treated mice had evidence of the probable protection of the liver and attenuating the systemic consequences of tumor growth, as evidenced by normalization of serum aspartate aminotransferase (ASAT), and lactate dehydrogenase (LDH) levels, compared to vehicle-dosed tumor-bearing animals. According to hematological analysis, treatment with GE-NPs caused an increase in red blood cells and hematocrit up to the healthy control levels. When a combination of GE-NPs (1 mg/ml) is injected into a mouse tumor and the tumor is irradiated by a laser beam, it leads to an increase in mice survival by more than 30% compared to GE-NPs-treated non-irradiated mice, and a decrease in the growth rate of the cancerous tumor. The observed therapeutic effect can be related to the photoacoustically-induced destruction of cancer cells significantly enhanced by the presence of the incorporated GE-NPs, because the laser-induced localized heating of mice skin has not exceeded 2 °C. Conclusions the efficiency of photoacoustic therapy of Lewis Lung carcinoma in mice using biocompatible carbon dots was demonstrated. Biocompatible GE-NPs own multimodal potential in cancer theranostics, including both photoacoustic imaging and therapy, by applying different irradiation conditions.